Prevention and potential remedies for antibiotic resistance: current research and future prospects - Khan, Rabiya Tabbassum; Sharma, Vanshika; Khan, Sofia Sharief; Rasool, Shafaq (Frontiers in Microbiology, 2024)
The increasing threat of antibiotic resistance and shrinking treatment options for infections have pushed mankind into a difficult position. The looming threat of the return of the pre-antibiotic era has caused a sense of urgency to protect and conserve the potency of antibiotic therapy. One of the perverse effects of antibiotic resistance is the dissemination of its causative agents from non-clinically important strains to clinically important strains and vice versa. The popular saying “Prevention is better than cure” is appropriate for tackling antibiotic resistance. On the one hand, new and effective antibiotics are required; on the other hand, better measures for the use of antibiotics, along with increased awareness in the general public related to antibiotic use, are essential. Awareness, especially of appropriate antibiotic use, antibiotic resistance, its dissemination, and potential threats, can help greatly in controlling the use and abuse of antibiotics, and the containment of antibiotic resistance. Antibiotic drugs' effectiveness can be enhanced by producing novel antibiotic analogs or adding adjuvants to current antibiotics. Combinatorial therapy of antibiotics has proven successful in treating multidrug-resistant (MDR) bacterial infections. This review aims to highlight the current global situation of antibiotic resistance and discuss the methods used to monitor, prevent, inhibit, or reverse bacterial resistance mechanisms in the fight against antibiotic resistance.